1985
DOI: 10.1152/jn.1985.54.5.1363
|View full text |Cite
|
Sign up to set email alerts
|

Epileptiform activity induced by changes in extracellular potassium in hippocampus

Abstract: Using extra- and intracellular recording techniques, we investigated the induction and frequency modulation of spontaneous epileptiform activity produced by changes in the concentration of extracellular potassium ([K+]o). This paper describes a quantitative relationship between [K+]o and the frequency of spontaneously occurring epileptiform events. Recordings were made from the CA3 subfield of the rat in vitro hippocampal slice preparation. Intracellular microelectrodes were filled with 2 M Cs2SO4 and connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
132
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(146 citation statements)
references
References 0 publications
14
132
0
Order By: Relevance
“…Many of them rely on blocking GABA A receptor mediated inhibition with drugs such as picrotoxin, bicuculline or penicillin (Dingledine and Gjerstad, 1979;Schwartzkroin and Prince, 1978). Convulsant treatments which do not block inhibition include 4-aminopyridine (Avoli et al, 1996;D'Antuono et al, 2002;Rutecki et al, 1987), elevated K + (Jiruska et al, 2010a;Rutecki et al, 1985;Traub and Dingledine, 1990) and low Mg 2+ (Anderson et al, 1986;Derchansky et al, 2008). Another acute and realistic model in vivo is brain trauma, which leads to electrographic seizures in the majority of animals (Topolnik et al, 2003).…”
Section: Acute Models Of Epilepsy-convulsant Drugsand Changes In Extrmentioning
confidence: 99%
“…Many of them rely on blocking GABA A receptor mediated inhibition with drugs such as picrotoxin, bicuculline or penicillin (Dingledine and Gjerstad, 1979;Schwartzkroin and Prince, 1978). Convulsant treatments which do not block inhibition include 4-aminopyridine (Avoli et al, 1996;D'Antuono et al, 2002;Rutecki et al, 1987), elevated K + (Jiruska et al, 2010a;Rutecki et al, 1985;Traub and Dingledine, 1990) and low Mg 2+ (Anderson et al, 1986;Derchansky et al, 2008). Another acute and realistic model in vivo is brain trauma, which leads to electrographic seizures in the majority of animals (Topolnik et al, 2003).…”
Section: Acute Models Of Epilepsy-convulsant Drugsand Changes In Extrmentioning
confidence: 99%
“…However, the pioneering studies made in Johnston's laboratory with single-electrode voltage-clamp recordings have demonstrated that the amplitude of the interictal responses recorded during application of medium containing 4AP, tetraethylammonium, or elevated [K + ] are characterized by reversal potentials that are more negative than those associated with reversal potentials of paroxysmal depolarization shifts induced by GABA A receptor antagonists (Rutecki et al, 1985(Rutecki et al, , 1987(Rutecki et al, , 1990. Hence, synaptic inhibition is operative in these in vitro models of interictal discharge.…”
Section: Fast Ca3-driven Interictal Activitymentioning
confidence: 99%
“…2 A) (see Figs. 3-7) (Rutecki et al, 1985). This [K ϩ ] o diminishes neuronal Cl Ϫ extrusion by decreasing the driving force for K-Cl cotransport, thereby making the GABA reversal potential more positive (Thompson and Gahwiler, 1989b).…”
Section: Contributions Of Synaptic Activities To Firing Rates Of Hippmentioning
confidence: 99%